STRATEGIES TO IMPROVE TEACHERS’ SELF-EFFICACY IN INDONESIAN INCLUSIVE ELEMENTARY SCHOOLS A LITERATURE REVIEW - Shoviana, Luluk (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2019)
ABSTRACTInclusive education (IE) has emerged worldwide since the United Nations held the international campaign of the World Declaration on Education for All. In 2003, the Indonesian government began to promote this new system by a new Law on the National Education System (Act N0. 20/ 2003) that directs its regions to have a minimum four inclusive schools. With the IE system, the school attendance of special need students (SNS) increased from 29,104 to 1,500,625. Previous studies suggest that the success of IE implementation depends on teachers. However, the results indicate that Indonesian teachers lack skills and knowledge that lead to their low levels of self-efficacy to support SNS in their classes. Many studies suggest the use of Bandura’s sources of self-efficacy theory to provide adequate related professional development programs for teachers. However, they partially discussed strategies to improve teachers’ self-efficacy. Thus, the current study aims to synthesize the existing literature on strategies to improve teachers’ self-efficacy. Adjustments to Indonesian inclusive education context are discussed.  Keywords: Inclusive Education, Self-Efficacy, Elementary School.